The genus Hintonelmis (Coleoptera: Elmidae: Elminae), new species and records - Polizei, Thiago T. S. [UNESP]; Barclay, Maxwell V. L. (Taylor & Francis Ltd, 2018)
Hintonelmis is a South American genus of Elmidae, comprising 11 species. Two further new species are here described and illustrated: Hintonelmis guianensis sp. nov. from Guyana, and Hintonelmis roellae sp. nov. from Brazil, can be distinguished from all other known members of the genus by their general colour pattern, some characters of pronotal and elytral sculpture, and the morphology of the male genitalia. The type material is deposited in the Natural History Museum, London, UK and Museum of Zoology of the University of Sao Paulo, Sao Paulo, Brazil. New distributional data for species of Hintonelmis are presented for the South of Brazil, Bolivia, Ecuador, and Guyana. We also provide an updated key for the genus species.
Keywords: Aquatic beetles; riffle beetles; Neotropical; South America; taxonomy